LabVIEW 2010 Computer Vision Platform Based Virtual Instrument and Its Application for Pitting Corrosion Study - Rogelio Ramos; Roumen Zlatev; Benjamin Valdez; Margarita Stoytcheva; Mónica Carrillo; Juan-Francisco García (Journal of Analytical Methods in Chemistry)
A virtual instrumentation (VI) system called VI localized corrosion image analyzer (LCIA) based on LabVIEW 2010 was developed allowing rapid automatic and subjective error-free determination of the pits number on large sized corroded specimens. The VI LCIA controls synchronously the digital microscope image taking and its analysis, finally resulting in a map file containing the coordinates of the detected probable pits containing zones on the investigated specimen. The pits area, traverse length, and density are also determined by the VI using binary large objects (blobs) analysis. The resulting map file can be used further by a scanning vibrating electrode technique (SVET) system for rapid (one pass) “true/false” SVET check of the probable zones only passing through the pit’s centers avoiding thus the entire specimen scan. A complete SVET scan over the already proved “true” zones could determine the corrosion rate in any of the zones.